Neonatal Morbidity by Week of Gestational Age for Twins Compared to Singletons: A Population-Based Cohort Study - Wolfe, Katherine; Tabangin, Meredith; Meinzen-Derr, Jareen; Snyder, Candice; Lewis, David; DeFranco, Emily (American Journal of Perinatology, 2014)
Objective Quantify neonatal morbidity by week of gestation for twins compared with singletons.Study Design We performed a population-based retrospective cohort study of all Ohio births from 2006 to 2007. Composite neonatal morbidity consisting of Apgar score < 7 at 5 minutes, assisted ventilation > 6 hours, neonatal transport, or seizures was compared between singletons and twins from 34 to 41 weeks.Results Neonatal morbidity was the lowest in twins delivered at 37 completed weeks and 2 weeks later for singletons at 39 weeks. Twin morbidity rapidly increased after 37 weeks and reached 15.8% at 41 weeks versus the singleton morbidity rate of 3.4% at 41 weeks. Twins delivered at 39 weeks and beyond were more than twice as likely to incur neonatal morbidity compared with singletons.Conclusion The lowest rate of neonatal morbidity occurs at 37 weeks for twins versus 39 weeks for singleton births. The increased risk after 37 weeks for twins accelerates at a faster rate compared with that for singletons born past 39 weeks.
Keywords: neonatal morbidity; birth timing; twins